Literacy and africanities: training experiences in the extension course read and write in school - Luciene Cerdas; Rejane Amorim (Temas em Educação e Saúde, 2018)
This article presents a training practice of literacy teachers in the "Extension Course read and writing: articulating knowledge, building practices", carried out from a theme that has been gaining increasing prominence in the education area, namely, Africanities, which emphasizing the marks of African culture in the construction of Brazilian culture. The potential of this action is socialized in the formation of literacy teachers and of graduates in Pedagogy who act as part of the course implementation team. Weekly, It brings together  students and teachers from Pedagogy and public school teachers in Rio de Janeiro to discuss issues  related to teaching in literacy, reading and writing, and to the construction of innovative practices in literacy, in such a way that initial and teachee's formation built in dialogue with these subjects. The subject of Africanities was approached from the perspective of the valorization of the roots of Brazilian culture that are of African origin, discussing ethnic-racial relations, conceptions of racial prejudices, in the name of the urgent and necessary respect for the different ways of being, of living and living together. A promising experience of working with this theme is based on two different proposals: the construction of the African Panõ and the making of the Abayomi doll, activities that have ivolved different languages, such as reading, drawing, painting and handicrafts. These actions demonstrated great training potential in the perspective of literacy in which curriculum integration as well as language as human interaction, are central assumptions.